The Distribution Pattern and Leaching Toxicity of Heavy Metals in Glass Ceramics from MSWI Fly Ash and Andesite Tailings - Yongya Wang; Xinyi Huang; Wei Wang; Tao Wu (Toxics, 2022)
The leaching of heavy metals (HMs) is the key factor affecting the resource utilization of municipal solid waste incineration (MSWI) fly ash. A novel fly ash and andesite-tailings-based (FAAT) glass ceramic is prepared with the full-component utilization of MSWI fly ash and andesite tailings. The effects of the content and distribution state of HMs on their leaching toxicity are studied by performing a sequential extraction procedure and leaching toxicity test. The results show that the MSWI fly ash content greatly impacts the HMs’ leaching toxicity in glass ceramics. Thus, the addition of MSWI fly ash must be maintained at below 20% so as to meet the class III groundwater standard. Furthermore, the different distribution states of Zn and Cr also affect their leaching toxicity. Zn suits the requirements for leaching toxicity only in a 2080c sample, while Cr fulfills the class III groundwater standard for all the glass ceramics. Since this finding is mismatched with the calculated potential ecological risk index of glass ceramics, the latter can only be used as a reference. Therefore, the results of the present study are of great significance in the vitrification application of MSWI fly ash.